Medicinal attributes of pyrazolo[1,5-a]pyrimidine based scaffold derivatives targeting kinases as anticancer agents - Nasser S.M. Ismail; Ghada M.E. Ali; Diaa A. Ibrahim; Amira M. Elmetwali (SpringerOpen, 2016)
Pyrazolo pyrimidines are fused heterocyclic ring systems which known as bioisosteres of adenine, that are necessary for every aspect of cell life. Pyrazolo[1,5-a]pyrimidines derivatives have been explored for their inhibitory activity towards a variety of protein kinase enzymes and their function as anticancer agents. This review to the best of our knowledge is the first assemblage on synthesis and medicinal aspects including structure activity relationships of pyrazolo[1,5-a]pyrimidines reported to date.